2016
DOI: 10.1007/s12603-015-0694-6
|View full text |Cite
|
Sign up to set email alerts
|

Food accessibility and perceptions of shopping difficulty among elderly people living alone in Japan

Abstract: The study concludes that elderly people's assessment of shopping difficulty is related to their food accessibility. Important food accessibility aspects include car or motorbike ownership, walking continuously for 1 km, poor eyesight, and having cooking skills and having someone to help with shopping. These physical activity restrictions have a greater influence on shopping difficulty than do either income or proximity to a supermarket.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…Living alone requires adequate physical function. However, it is reported that the elderly who live and eat alone have a significantly lower food diversity and food intake frequency than those who eat together their family often [35], and have lower food accessibility, related to shopping difficulty [36]. Therefore, even if the elderly living alone have independent lives, there is a concern that the quality of their food intake may deteriorate their nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Living alone requires adequate physical function. However, it is reported that the elderly who live and eat alone have a significantly lower food diversity and food intake frequency than those who eat together their family often [35], and have lower food accessibility, related to shopping difficulty [36]. Therefore, even if the elderly living alone have independent lives, there is a concern that the quality of their food intake may deteriorate their nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…In many rural areas in Japan, small local stores have been forced to close because of development of large-scale stores in suburban areas [22]. This situation, often described as a "food desert" problem, could have increasingly serious consequences because of the aging and shrinking population and the closing of local supermarkets in rural areas [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported no relationship between dietary habits and objective accessibility such as distance. Some studies have shown that perceived access to food retailers or difficulties with shopping are related to fruit/vegetable intake frequency or dietary variety scores (DVS; Fukuda et al, 2017;Ishikawa et al, 2016;Nakamura et al, 2017;Yoshiba et al, 2015). Another study reported the opposite results -that a higher intake frequency of vegetables and fruits was noted, even in areas with low objective accessibility, whereas a low intake frequency of vegetables and fruits was noted in areas with low perceived accessibility (Yamaguchi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The threshold of low accessibility based on the distance from the grocery stores may depend on population or geographical characteristics. In rural areas, where a car or automobile is required for shopping, >1 km is often used as the threshold (Ishikawa et al, 2016;Nakamura et al, 2017;Sharkey et al, 2010), whereas elderly people primarily walk to food stores in urban/suburban areas. Therefore, their shopping behaviour will be limited to grocery stores within a shorter distance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation